Cold storage, Alaska - Straley, John, 1953- (Soho Crime, 2014)
"Cold Storage, Alaska, is a remote fishing outpost where salmonberries sparkle in the morning frost and where you just might catch a King Salmon if you're zen enough to wait for it. Settled in 1935 by Norse fishermen who liked to skinny dip in its natural hot springs, the town enjoyed prosperity in the mid-20th Century, at the height of the frozen fish boom. But now the cold storage plant is all but abandoned and the population is shrinking every day. Clive "The Milkman" McCahon returns to his tiny Alaska hometown after a 7-year jail stint for dealing coke. He has a lot to make up to his younger brother, Miles, who has dutifully been taking care of their ailing mother--and, really, all of Cold Storage--Miles is a Physician's Assistant and the closest thing to a doctor this side of Sitka. But Clive doesn't realize the trouble he's bringing home. He's reformed now, and his dream is to open a bar-slash-church (a Cold Storage ordinance requires there to be as many churches in town as there are bars). Clive's vengeful old business partner is hot on his heels, a stick-in-the-mud State Trooper is dying to bust Clive for narcotics, and, to complicate everything, Clive might be going insane--lately, he's been hearing animals talking to him. Will his arrival in Cold Storage be a breath of fresh air for the sleepy, depopulated town? Or will Clive's arrival turn the whole place upside-down?"--